1, 2‐Bis(diarylmethylene)cyclobutane as an Effective Building Block for Aggregation‐Induced Emissive Materials. Issue 2 (27th December 2016) - Eguchi, Hiroshi; Nishiyama, Hiroki; Inagi, Shinsuke; Tomita, Ikuyoshi
Abstract: Solid‐state luminescent properties of 1, 2‐bis(diarylmethylene)cyclobutanes are described. A series of 1, 2‐bis(diarylmethylene)cyclobutanes were prepared by a regio‐ and chemoselective cyclodimerization of 1, 1‐diarylallenes, mediated by a stoichiometric amount of Ni(PPh3 )4, in 64–77 % yields. These dimers exhibit excellent aggregation‐induced emission (AIE) properties with a quantum yield that reaches 85 % in the solid state. The crystal structures of the products revealed that the peripheral benzene rings suppress the intermolecular π–π stacking, resulting in remarkably efficient luminescence. Abstract : A series of 1, 2‐bis(diarylmethylene)cyclobutanes has been successfully prepared by a regio‐ and chemoselective cyclodimerization of 1, 1‐diarylallenes mediated by a tetrakis(triphenylphosphine)nickel complex. These compounds exhibit excellent aggregation‐induced emission (AIE) properties with a quantum yield that reaches 85 % in the solid state.